On linearly topological structure and property of fuzzy normed linear space - Xiao, Jianzhong; Zhu, Xinghua (Fuzzy sets and systems, 2002)
In this paper, the simplified definition of fuzzy normed linear space is introduced; the different structure of fuzzy normed linear space with variable right norm R is discussed in terms of topological vector space, and its properties such as compactness, completeness and density are studied under more general left norm L and right norm R; as application, the linearly topological structure of Menger PN space is obtained.